‘Theology on Its Knees’: The Arts as Religion - Marsh, Clive (Reviews in religion and theology, 2000)
Books reviewed in this article: Paul Corby Finney (ed.), Seeing Beyond the Word: Visual Arts and the Calvinist Tradition David Morgan, Protestants and Pictures: Religion, Visual Culture, and the Age of American Mass Production Richard Viladesau, Theological Aesthetics: God in Imagination, Beauty, and Art